Ethnomathematics Exploration of Geometry Concepts in Traditional Games in Karanganyar Regency - Aulya, Sholihatun Nisa; Exacta, Annisa Prima (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The purpose of this study is to describe the concept of geometry concepts contained in traditional games in Karanganyar Regency such as: engklek, kites, and marbles. This research uses qualitative research with an ethnographic approach. The data collection methods used in this research are observation, documentation and interviews. The results of this study indicate that in traditional games in Karanganyar district there is the concept of geometry. The geometry concepts contained are flat shapes (square, rectangle, triangle, kite, semicircle and circle), space shapes (tube and ball), geometry transformation (reflection), and congruence. The concept of geometry is illustrated in the game arena and game tools.